Analisis Pengaruh Kelembagaan Kelompok Tani terhadap Produksi Gula Kelapa di Kecamatan Cilongok Kabupaten Banyumas - Aulia, Wina Taskia; Istiqomah, Istiqomah; Barokatuminalloh, Barokatuminalloh (Lingka Ekonomika, 2023)
Banyumas Regency has one of the leading commodities, namely coconut plantations. One of the sub-districts in Banyumas Regency which is the center of the coconut sugar industry is Cilongok District. This is indicated by the higher production numbers compared to other regions. The coconut sugar industry is able to absorb a lot of workers. However, the production volume of each craftsman varies. Meanwhile, craftsmen make their daily living by producing coconut sugar. Therefore, it is necessary to carry out research with the title "Analysis of the Institutional Influence of Farmer Groups on Coconut Sugar Production in Cilongok District, Banyumas Regency". The aim of this research is to analyze the influence of farmer group institutions, capital, number of trees, and technology on coconut sugar production. The results of this research show that: 1) Capital and number of trees have a significant positive effect on coconut sugar production, 2) Farmer group membership and technology do not have a significant effect on coconut sugar production. The implication of this research is that to increase coconut sugar production, the role of farmer groups needs to be increased so that craftsmen are motivated to increase coconut sugar production. Apart from that, craftsmen need to apply information obtained from farmer groups. The role of financial institutions and cooperatives is needed so that craftsmen are not only tied to loans provided by collectors. The government's role is also needed in providing support in the form of technology to expedite the coconut sugar production process.